2011
DOI: 10.1371/journal.pntd.0000977
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Antibody and Cytokine Markers for Leprosy Nerve Damage and Reactions in the INFIR Cohort in India

Abstract: BackgroundThe ILEP Nerve Function Impairment in Reaction (INFIR) is a cohort study designed to identify predictors of reactions and nerve function impairment (NFI) in leprosy.Aim of the StudyAntibodies to mycobacteria, nerve components and serum cytokine were measured as potential markers for their possible association with reactions and NFI.Patients and Methods303 newly diagnosed leprosy patients from two centres in North India were enrolled. Antibodies to PGL-1, LAM (IgG1 and IgG3), ceramide, S100 and TNFα l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 28 publications
2
22
0
6
Order By: Relevance
“…Elevated levels of TNF-a and IFN-c have been observed in leprosy and in lepra reactions [10,13,27]. The present study also showed elevated TNF-a and IFN-c levels in LN patients which could be due to exaggerated cell mediated immunity (CMI) that can lead to both a beneficial effect of clearing of bacilli as well as the adverse effect of producing demyelination and subsequent loss or impairment of nerve function [6]. There was no significant difference in the levels of plasma TNF-a and IFN-c between PB and MB cases suggesting that neuropathy in leprosy involves both cytokines to the same extent though they present different bacterial load and clinical classification.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Elevated levels of TNF-a and IFN-c have been observed in leprosy and in lepra reactions [10,13,27]. The present study also showed elevated TNF-a and IFN-c levels in LN patients which could be due to exaggerated cell mediated immunity (CMI) that can lead to both a beneficial effect of clearing of bacilli as well as the adverse effect of producing demyelination and subsequent loss or impairment of nerve function [6]. There was no significant difference in the levels of plasma TNF-a and IFN-c between PB and MB cases suggesting that neuropathy in leprosy involves both cytokines to the same extent though they present different bacterial load and clinical classification.…”
Section: Discussionsupporting
confidence: 67%
“…Association of A/A homozygous genotype was also observed in HIV-PN as compared to HIV group (p < 0.05, OR = 6.5, CI = 2. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. When LN group was segregated we found a significant association of IFN-c +874 A/A genotype in MB leprosy group (p < 0.05, OR = 8, CI = 3.1-21) and not in PB group as compared to HS.…”
Section: Ifn-c +874 T/a Polymorphismmentioning
confidence: 99%
See 1 more Smart Citation
“…This evidence of increased auto antibodies to myelin and glycosphingolipid components of nerve in treated leprosy patients indicates that nerve damage continues as an autoimmune response to multiple nerve components even after a patient has completed leprosy treatment [25,38]. In a study of 303 multibacillary leprosy patients, ceramide antibody was elevated in patients with old sensory nerve damage [39] suggesting that autoantibodies may not be involved in the initiation of nerve damage but play an important role in the propagation of nerve damage. During the course of treatment and thereafter, various nerve antigens may be presented to the immune system which trigger autoimmune mechanisms whereby nerve damage is perpetuated.…”
Section: Discussionmentioning
confidence: 99%
“…Corollarily, as patients with impaired nerve function typically have high levels of anti-PGL-I IgM and IgG, serological evaluation may also assist in identifying individuals with nerve damage ( Table 3). The association between high antibody titers and nerve damage highlights the need to detect and treat serologically positive individuals as soon as possible (45) . Serum antibodies can also be a useful measure of the effectiveness of treatments (4) (26) (27) ( Table 3).…”
Section: Serological Tools In Evaluating Multidrug Therapymentioning
confidence: 99%